2016
DOI: 10.1002/cjce.22386
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation with Lysozyme: A Non‐Enzymatic Application

Abstract: Bioflocculants have been previously recognized as an alternative to synthetic polymers due to their renewable sources and biodegradability. In this study, the flocculating activity of lysozyme on kaolin suspensions was investigated and compared to a known flocculant, a cationic polyacrylamide. Lysozyme was found to significantly aid in the flocculation of kaolin particles. The flocculating activity of lysozyme on kaolin was affected by the pH of the suspensions, while the addition of Mg2+ and Ca2+ ions did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Researchers apply it for colloidal nanoparticle based solutions in medicine, pharmaceutical products, chemical manufacturing, mineral processing, soil and water purification. [8,[39][40][41][42][43] ZP influence intra-cellular trafficking and cellular stabilization in in vitro experiments. [33,[44][45][46][47][48][49] WoS assigned most articles to pharmacology and pharmacy (777), followed by physical chemistry (659), multidisciplinary materials science (583), chemical engineering (515), and multidisciplinary chemistry (493) is the last category in the top five.…”
Section: Applicationsmentioning
confidence: 99%
“…Researchers apply it for colloidal nanoparticle based solutions in medicine, pharmaceutical products, chemical manufacturing, mineral processing, soil and water purification. [8,[39][40][41][42][43] ZP influence intra-cellular trafficking and cellular stabilization in in vitro experiments. [33,[44][45][46][47][48][49] WoS assigned most articles to pharmacology and pharmacy (777), followed by physical chemistry (659), multidisciplinary materials science (583), chemical engineering (515), and multidisciplinary chemistry (493) is the last category in the top five.…”
Section: Applicationsmentioning
confidence: 99%
“…Failure of chitosan flocculants in an erosion control study was partially attributed to relatively low MW of chitosan compared to synthetic polymeric flocculants. Proteins are being increasingly recognized for their potential as biobased flocculants. Proteins derived from agricultural byproducts can be inexpensive, and some, such as hemoglobin from slaughterhouse blood, display good flocculant properties.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Application of various types of these "biopolymers" as kaolinite clay occulants has been comprehensively researched. [14][15][16][17][18][19] A few studies have reported the effectiveness of various biopolymers to improve otation and occulation processes in mineral processing. found that chitosan (the amine-based polysaccharide) could depress chalcopyrite (copper ore) selectively in the otation of copper-lead ores.…”
Section: Introductionmentioning
confidence: 99%
“…18 Y. C. Ho (2010) 12 considered the effect of pectin for occulation of kaolinite particles, and it was found that pH 3 was the optimum treatment condition for pectin occulating activity. 26 Bonilla (2015-2017) 14 studied the effectiveness of proteins (protamine and lysozyme) on the dewatering of pulp and paper mill biosludge and found that lysozyme showed higher occulating activity. 14,27,28 Previous studies only focused on kaolinite clay particles and the potential of biopolymers to mitigate other types of phyllosilicates in otation and dewatering has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation